1997
DOI: 10.1007/bf01285550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dantrolene on KCl- or NMDA-induced intracellular Ca2+ changes and spontaneous Ca2+ oscillation in cultured rat frontal cortical neurons

Abstract: Dantrolene has been known to affect intracellular Ca2+ concentration ([Ca2+]i) by inhibiting Ca2+ release from intracellular stores in cultured neurons. We were interested in examining this property of dantrolene in influencing the [Ca2+]i affected by the NMDA receptor ligands, KCl, L-type Ca2+ channel blocker nifedipine, and two other intracellular Ca2(+)-mobilizing agents caffeine and bradykinin. Effect of dantrolene on the spontaneous oscillation of [Ca2+]i was also examined. Dantrolene in microM concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…Dantrolene, a blocker of ryanodine receptor-dependent Ca 2+ release, attenuates the NMDA-mediated rise in intracellular Ca 2+ (66). As in our previous experiments with acute hippocampal slices, dantrolene did not change glutathione, PEA, or taurine efflux rates, suggesting that the efflux rate is not regulated by ryanodine receptor-dependent Ca 2+ release.…”
Section: Discussionsupporting
confidence: 78%
“…Dantrolene, a blocker of ryanodine receptor-dependent Ca 2+ release, attenuates the NMDA-mediated rise in intracellular Ca 2+ (66). As in our previous experiments with acute hippocampal slices, dantrolene did not change glutathione, PEA, or taurine efflux rates, suggesting that the efflux rate is not regulated by ryanodine receptor-dependent Ca 2+ release.…”
Section: Discussionsupporting
confidence: 78%
“…1, A and D); this staining pattern was observed in the majority of the cells (Table I). The level of [Ca 2ϩ ] i in rat cortical neurons has been established previously to be ϳ50 nM in resting cells and above 300 nM upon KCl activation (27). We observed that activation of cultured cortical neurons by KCl induces CacyBP translocation mainly to the perinuclear region (Fig.…”
Section: Methodsmentioning
confidence: 49%
“…The intracellular Ca 2ϩ level in cultured rat cortical neurons is ϳ50 nM and upon KCl stimulation increases to above 300 nM (27). Similar low levels of resting [Ca 2ϩ ] i were measured in hippocampal neurons (80 nM) (28) and hypothalamic neurons (54 or 69 nM) (29,30 (32).…”
Section: Discussionmentioning
confidence: 55%
“…In agreement, exposure of eosinophilic leukemia cells or platelets to a Ca 2+ -ionophore did not release DHA while releasing AA through cPLA 2 activation ( 9 ), and chronic NMDA administration to rats increased cPLA 2 -IVA but not iPLA 2 -VI expression in brain ( 43 ). Under some in vitro conditions, acute NMDA receptor activation may release Ca 2+ from intracellular stores by Ca 2+ -induced Ca 2+ release (CICR) ( 44,45 ), which may indirectly stimulate iPLA 2 (46)(47)(48). However, our in vivo data do not support this signaling pathway with the dose of NMDA administered.…”
Section: Discussionmentioning
confidence: 62%